A Comparative Analysis of Cardiovascular Events Associated With Acalabrutinib Versus Ibrutinib in Chronic Lymphocytic Leukemia: Insights From a Global Federated Network - Abdulrahman Majrashi; Ying X. Gue; Alena Shantsila; Stella Williams; Catrin Tudur Smith; Gregory Y. H. Lip; Andrew R. Pettitt (Pharmacology Research & Perspectives)
ABSTRACT Chronic lymphocytic leukemia (CLL) is the most common form of leukemia in adults, characterized by the accumulation of dysfunctional lymphocytes. Ibrutinib, a first‐generation Bruton tyrosine kinase (BTK) inhibitor, has significantly improved CLL treatment but is associated with adverse cardiovascular events such as atrial fibrillation (AF) and hypertension (HTN). Second‐generation BTK inhibitors (BTKi) such as acalabrutinib were developed to have greater selectivity for BTK to reduce off‐target effects and improve safety. Comparative real‐world data between ibrutinib and second‐generation BTKi are limited. This study analyzed data from the TriNetX Global Collaborative Network to compare cardiovascular outcomes in CLL patients who received ibrutinib or acalabrutinib. The two groups were well‐balanced using propensity score matching. The outcomes examined included new‐onset AF, HTN, reported heart failure, ventricular arrhythmias, bleeding, and all‐cause mortality. The incidence of AF/flutter was lower for acalabrutinib compared to ibrutinib [5.8% vs. 11.7%; HR 0.59 (95% CI 0.43–0.83); p = 0.002]. The incidence of HTN was also lower in the acalabrutinib cohort [15% vs. 26.3%; HR 0.65 (95% CI 0.53–0.81); p < 0.05]. The incidence of heart failure, ventricular arrhythmia, bleeding events, or all‐cause mortality did not differ after 3 years of treatment with acalabrutinib or ibrutinib, respectively. Our findings indicate that acalabrutinib has a more favorable cardiovascular toxicity profile compared to ibrutinib; therefore, validating the ELEVATE‐RR trial in a real‐world setting.